Behavioural and neuropsychiatric disturbance in three clinical subtypes of frontotemporal dementia: A Clinical Research Center for Dementia of South Korea‐FTD Study. (March 2017) - Park, Moon Ho; Kim, Eun‐Joo; Park, Kyung Won; Kwon, Jae Cheol; Ku, Bon D.; Han, Seol‐Heui; Kim, SangYun; Yang, Dong Won; Na, Duk L.; Choi, Seong Hye
Abstract : Objectives: To characterise the behavioural and neuropsychiatric disturbances of patients with three clinical subtypes of frontotemporal dementia (FTD): behavioural variant FTD (bvFTD), semantic dementia (SD) and progressive non‐fluent aphasia (PNFA). Methods: Consecutive series of 66 patients with bvFTD, 58 patients with SD and 21 patients with PNFA were compared using the Frontal Behavioural Inventory (FBI) and the Neuropsychiatric Inventory (NPI). Results: Patients with bvFTD had more behavioural and neuropsychiatric disturbances than patients with PNFA based on the total scores of FBI and NPI. When comparing subtotal and item scores of FBI and NPI, there were some significant differences among three clinical subtypes of FTD. Conclusion: There are some distinct patterns of behavioural and neuropsychiatric disturbance among three clinical subtypes of FTD.